Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve the system by substitution:7x-3y=-254x+5=y(__ , __)

Sagot :

EXPLANATION

Considering the system of equations:

(1) 7x - 3y = -25

(2) 4x + 5 = y

Isolating x from the first equation:

Adding +3y to both sides:

7x = -25 + 3y

Dividing both sides by 7:

x = -25/7 + 3y / 7

Substituting x from (1) in (2):

4(-25/7 + 3y/7) + 5 = y

Applying the distributive property and removing the parentheses:

-100/7 + 12y/7 + 5 = y

Adding like terms:

-65/7 + 12y/7 = y

Subtracting -12y/7 to both sides:

-65/7 = y - 12y/7

Adding like terms:

-65/7 = -5y/7

Multiplying both sides by -7/5:

(-65/7)*(-7/5)= y

Switching sides:

y = (-65/7)*(-7/5)

Multiplying terms:

y= 13

Substituting y= 13 in (1):

x= -25/7 + 3*(13)/7

Multiplying like terms:

x= -25/7 + 39/7

Adding the fractions:

x= 2

The solution to the system of equations is:

(x,y) = (2,13)

We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.